Enhancing Breast Milk Production and Body Weight through Complementary Oxytocin Massage Therapy - Wulandari, Amri; Agustin, Nisa Amelia; Putrianti, Berlina (STIKep PPNI Jawa Barat, 2025)
Background: Newborns' nutrition and development depend on breast milk, but many moms don't produce enough, which is bad for their babies' health and development. One non-pharmacological approach that has been shown to improve milk ejection is oxytocin massage. Few research have investigated its combined impact on low-resource settings and newborn weight increase, despite indications of its usefulness. Objective: Specifically, we want to know how well oxytocin massage treatment works as a supplement to increase milk supply and boost baby weight gain. Methods: A quasi-experimental research was carried out in Sukabumi, West Java, with 70 postpartum moms and their infants aged 0-3 months. The study used a pre-test and post-test control group design. Two groups were established: one that received regular postpartum care and another that received oxytocin massage daily for seven days. We assessed breast milk supply and baby weight before and after the intervention. The data was examined by means of multivariate regression analysis, paired t-tests, and independent t-tests. Results: In comparison to the control group, the intervention group demonstrated a notable rise in both baby body weight (mean difference: 0.5 kg, p = 0.001) and breast milk production (mean difference: 240 mL/day, p < 0.001). Treatment with oxytocin massage continued to be associated with better results even after controlling for factors such as mother age, parity, and level of education. Conclusion: Boosting breast milk supply and promoting newborn weight growth are both achieved with complementary oxytocin massage treatment. This intervention provides a practical and affordable way to enhance the health of newborns and the success of breastfeeding, especially in areas with limited resources. The advantages over the long run and its applicability to more diverse groups should be the focus of future research